The Meaning and Impact of Screen Time (ST) on Emotional Regulation in Children Aged 5-6 Years - Hasanah, Nur; Salasatun Ashar, Dinar; Astarin, Wd. Syamzahrah (JURNAL PENA PAUD, 2025)
Increased screen time (ST) in children aged 5–6 years has various effects on their emotional development. Excessive ST can hinder children's ability to recognize and control their emotions. This study aims to explore the meaning and impact of screen time (ST) on children's emotional regulation. The study employed a descriptive qualitative approach, utilizing interviews and observation techniques with six parents who have young children. Informants were selected using purposive sampling with the following criteria: (1) parents with different educational backgrounds (high school and bachelor's degree) to see variations in perceptions of ST and children's emotional regulation; (2) parents whose children routinely used ST for 5–8 hours per day; and (3) communicative parents, namely mothers and fathers of children aged 5–6 years who were willing to participate in the study. The results showed that parents perceived ST as a means of entertainment, learning, and calming their children. These findings were obtained through a thematic analysis of interview transcripts and observations, which revealed three primary meanings. ST evoked ambivalent emotional reactions: children displayed positive responses, such as happiness, joy, calmness, and imitative behavior, when using ST; however, they also showed adverse reactions, including anger, tantrums, sadness, or bargaining, when ST was stopped. Excessive use without time limits can weaken children's ability to control their emotions. ST management strategies are implemented by setting time limits, determining goals, and considering the child's condition. These findings show that ST plays a dual role in children's emotional regulation.